Czy godność człowieka jest zasadą prawną? - Sobczak, Witol (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
Human dignity is at the same time a theological, philosophical and legal category. Subject literature emphasizes that the researchers into the issue of dignity derive it from religion or natural law. The notion of ‘human dignity’has recently become exceptionally important in the considerations of lawyers, particularly of those involved in European law, mainly the Community (Union) law, as well as in theological and philosophical circles. There are two reasons for that. On the one hand, it seems to be a consequence of the attention paid to ‘human dignity’ in the Charter of Fundamental Rights of the European Union, where it is perceived as both a fundamental right and the source of all human rights. Secondly, the social teachings of the Catholic Church have started making reference to this notion.